2011
DOI: 10.1007/s10346-011-0260-1
|View full text |Cite
|
Sign up to set email alerts
|

Landslide hazard zoning along Himalayan Kaghan Valley of Pakistan—by integration of GPS, GIS, and remote sensing technology

Abstract: This paper presents a methodology for developing a landslide hazard zonation map by integration of global positioning system (GPS), geographic information system (GIS), and remote sensing (RS) for Western Himalayan Kaghan Valley of Pakistan. The landslides in the study area have been located and mapped by using GPS. Eleven causative factors such as landuse, elevation, geology, rainfall intensity, slope inclination, soil, slope aspect, distances from main road, distances from secondary roads, and distances from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…When the distance was larger than 4000 m, no landslide was found in field survey, the influence degree dropped to the minimize value, 0. In mountainous area, road may artificially cut towards the steep slopes which might cause high landslide occurrence in the near distances from the road [41].…”
Section: In Terrain Cutting Groupmentioning
confidence: 99%
“…When the distance was larger than 4000 m, no landslide was found in field survey, the influence degree dropped to the minimize value, 0. In mountainous area, road may artificially cut towards the steep slopes which might cause high landslide occurrence in the near distances from the road [41].…”
Section: In Terrain Cutting Groupmentioning
confidence: 99%
“…It was also observed that the two wells (20 and 26) where acifluorfen was not detected showed rank 1st, which represents the greatest leaching. There could be two possibilities for the fact that acifluorfen was not detected in these four wells (15,20,26, and 42) despite higher leaching ranks given to these wells by ArcPRZM-3. Firstly, some other pesticide (like bentazon) might have been applied on these crops instead of acifluorfen.…”
Section: Sensitivity Analysis For Arcprzm-3 Input Parametersmentioning
confidence: 98%
“…The major crops in the study area are soybeans, rice, and sorghum. The percentages of areas utilized in Randolph, Independence, and Woodruff counties for growth of (i) soybeans are 16,20, and 36%, (ii) rice are 12, 6, and 22%, and (iii) sorghum are 2, 2, and 16%, respectively [38].…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Geospatial technologies like the use of GIS, Global Positioning System (GPS), and Remote Sensing (RS) are useful in the hazard assessment, risk identification, and disaster management for landslides. GPS is a space-based global navigation satellite system which provides the information of position and time anywhere in the world in all weather conditions (Akbar and Ha 2011). Previous studies showed the application of GPS for mapping and identifying landslide zones.…”
Section: Introductionmentioning
confidence: 99%